A systematic study of uranium in groundwater and its correlation with other water quality parameters. Issue 3 (30th December 2021) - Srivastava, Mansi; Srivastava, P. K.; Kumar, Dharmendra; Kumar, Ajay
Abstract: A parametric investigation was carried out to estimate the Uranium concentration and other associated water quality parameters for the groundwater in Deoghar district, Jharkhand. A total of 150 groundwater samples have been collected from dig wells, hand pumps, tube wells, etc. for the pre and post-monsoon seasons. A Quantalase Uranium analyzer was used to measure the uranium concentration. The distribution of pH, TDS, DO, nitrate, sulfate, uranium, along with the radiation, has been determined. It was found that the uranium concentration in groundwater varies from 0.10 to 11.30ppb in pre-monsoon and 0.15–6.50ppb in the post-monsoon, which is well below the normal tolerance limit (i.e.30 μg/l WHO). This low availability of Uranium has been attributed to the existence of a lesser number of rocks containing uranium as a source in that area. An attempt has been made to correlate the uranium concentration with the water quality parameters for both seasons. The correlation data reveals that ORP, nitrate, phosphate, calcium, and magnesium show a positive correlation with uranium concentration for both seasons; on the other hand TDS, EC, temperature, DO, fluoride, and chloride show negative correlation. The positive correlation implies that uranium may be present in groundwater as a dissolved salt of these parameters. Comparative studies for the parameters have been done for both the seasons and various factors have been discussed for the occurrence of the same. The annual effective dose associated with the ingestion of uranium by the population of the region has been estimated using USEPA equations. HIGHLIGHTS: Cancer risk assessment. Ground water analysis. LED fluorimeter. Uranium correlation matrix. Graphical Abstract